Climate change and its impact on the vegetation cover in the Basiyah district - Dr. Jasb Kazim Abdul-Hussein (Journal of College of Education, 2025)
The study of climate change is one of the most important means used to understand the degradation of vegetation under population growth and exploitation or through human activities at accelerating rates. Vegetation depending on greenness indices. Therefore, vegetation is an indicator and measure of environmental degradation, changes in vegetation have a significant impact on land cover and uses in general. Natural phenomena of the study area using GIS. The study area is located in the northeastern part of the southwestern desert of Iraq, astronomically located between the two circles of latitude (َ32 29 ْ - َ51 30 ْ ) north and longitude( َ30 45 ْْ ْ), but it is located in the east. He included boundaries towards Basyah belonging to Salman's judgment within the province of Muthanna.
Keywords: Climate change, vegetation, desertification